(E)-(2,5-Difluorobenzyl)[(2-ethoxynaphthalen-1-yl)methylidene]amine - Ayşen Alaman Ağar; Mustafa Macit; Şamil Işık; Merve Pekdemir; Mustafa Serkan Soylu (Acta Crystallographica Section E, 2013)
In the title molecule, C20H17F2NO, which adopts an E conformation with respect to the imine C=N double bond, the mean planes of the naphthalene ring system and the difluorophenyl ring form a dihedral angle of 85.82 (7)°. An intramolecular C—H...N hydrogen bond occurs. In the crystal, weak C—H...F hydrogen bonds link the molecules into zigzag chains along [010].